2021
DOI: 10.1177/0886260521997941
|View full text |Cite
|
Sign up to set email alerts
|

Imprecision About Body Mechanics When Child Witnesses Are Questioned About Sexual Abuse

Abstract: In child sexual abuse cases, a central part of the child’s testimony is their description of the abuse episode. However, it is often difficult for children to describe the body mechanics of abuse, and miscommunications are likely to occur. In the present study, we examined questions about the mechanics of abuse in trial transcripts ( N = 63) to identify sources of miscommunication ( N = 130) between attorneys and children (5–12 years old, M age at trial = 9.44, SD = 1.97). We found that both attorneys and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…This may underestimate the false “no” problem when children are questioned about maltreatment. Second, we combined the negative polarity item “any” with the vague term “thing” in the paired yes–no questions (e.g., “Did you see anything?”), and this likely increased children’s rejection rate (Heritage et al, 2007; Sullivan et al, 2021). Future work can tease apart the various aspects of yes–no questions that pull for “no” responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may underestimate the false “no” problem when children are questioned about maltreatment. Second, we combined the negative polarity item “any” with the vague term “thing” in the paired yes–no questions (e.g., “Did you see anything?”), and this likely increased children’s rejection rate (Heritage et al, 2007; Sullivan et al, 2021). Future work can tease apart the various aspects of yes–no questions that pull for “no” responses.…”
Section: Discussionmentioning
confidence: 99%
“…Yes–no questions that contain “polarity items” may be particularly likely to pull for false “no” responses. Examining trial transcripts of 5- to 12-year-old children testifying in child sexual abuse cases, Sullivan and colleagues (2021) identified miscommunications between the attorney and child regarding the body mechanics of abuse. In one-third of the miscommunications, attorneys initially failed to elicit abuse information using vague terms such as “some,” “any,” and “ever” (e.g., “Did something happen to you in the bathroom?”), also known as “polarity items.”…”
Section: The Pros and Cons Of Pairing Yes–no Questions With Invitationsmentioning
confidence: 99%
“…Although changing "any" to "some" largely solved the problem in Heritage and colleagues' study (2007), questions with "some" may still be problematic because of vagueness, particularly when they are asked of children. Examining attorney-child interactions in court, Sullivan et al (2022) found that miscommunications frequently involved attorneys' use of yes-no any/some questions: children initially answered "no" and then subsequently answered more specific questions in ways that contradicted their initial denial. Sullivan et al (2022) suggest that both "some" and "any" questions are often vague, making it difficult for children to search their memory for specific details.…”
Section: Implied Requests For Wh-information In Yes-no Questionsmentioning
confidence: 99%
“…In addition, interviewers often use touch to introduce the abuse topic when asking screening questions. Researchers studying children’s reports of experienced touch have observed children often deny touch (Bruck, 2009; Quas & Schaaf, 2002; Sullivan et al, 2022), and surmise this could be partially attributable to children having underextended definitions of touch . Children may initially understand touch as referring only to manual touch, thus excluding nonmanual touch and touching with an object.…”
Section: Developing Definitions Of Touchmentioning
confidence: 99%
“…Walker (2013) related a case in which the child disclosed touching of the breasts, and when asked by police “Did he touch you anywhere else?” responded “no,” but later disclosed genital–genital contact: “the child explained that touching was ‘with fingers’” (p. 136). In a field study examining 5- to 12-year-old children questioned about sexual abuse in criminal trials, Sullivan et al (2022) found that questions about touch accounted for 18% of miscommunications, that is, exchanges in which children were inconsistent, uninformative, or insufficiently detailed.…”
Section: Developing Definitions Of Touchmentioning
confidence: 99%